English presentation tasks in improving students' speaking skills at vocational boarding school - Setiyawan, Heru; Anwar, Choiril (Universitas Islam Sultan Agung, 2025)
Educational institutions must continue to develop effective learning methods, such as presentation tasks that combine theory and practice. In English learning, apart from language skills, soft skills such as communication, conversation, collaboration, leadership, and problem-solving are very important. Vocational IDN Boarding School has set out to provide quality education and continues to improve learning methods that are different from other schools. This research aims to find out how students perceive the presentation of the English presentation task learning in English learning methods for improving students' speaking skills at a vocational boarding school. In this study, qualitative data were used for analyzing it. Data collection in this research used interviews methods, and involved 20 students from grades 10 and 11. The result reveals that the implementation of presentation tasks in English has gone well. Students are more motivated to practice speaking English to improve their speaking skills. The researchers found the novelty that some students’ implementation of presentation didn’t use the grammar (pattern sentence) and lack of pronunciation. It is hoped that the results of this research can provide nuance or valuable things for presentation development and learning practices in the world of education and will be able to contribute to the literature on English learning in particular and the development of soft skills.